(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The present study aimed that evaluation antihyperlipidemic activity of Salacia oblonga, Salacia roxbhurgii and Lagerstroemia parviflora individually and combined plants extracted poly herbal extraction and screened for phytochemical study performed Preliminary Phytochemical analysis of crude extracts for Salacia oblonga, Salacia roxbhurgii and Lagerstroemia parviflora for Antihyperlipidemic activity by Triton X 100 Induced Hyperlipidemia model, High Fat Diet (FD) induced hyperlipidemic model, by estimating the Total Cholesterol, Triglycerides, HDL-C, LDL-C, VLDL-C. Phytochemical investigation reveals the presence of alkaloids, flavanoids, saponins, tannins, steroids, triterpinoids, carbohydrates and glycosides in poly herbal methanolic extraction and individual plant extraction, In acute toxicity studies no mortality was observed with either of the extracts even at the dose level of 2000mg/kg body weight. In the present study, the methanol extracts of three plants reduced (Total Cholesterol, Triglycerides, LDL-C, VLDL-C reduced significantly in poly herbal extraction when compared with individual extraction HDL-C was increased in poly herbal extraction) the cholesterol and triglycerides in a manner similar to the reduction facilitated by atorvastatin. The hypolipidemic activities of atorvastatin and the methanol extract of individual and polyherbal extraction were evident in both synthesis and excretory phases of triton-induced hyperlipidemia in rats.